2018
DOI: 10.12659/msm.909684
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/Calmodulin-Dependent Protein Kinase II (CaMKII) Increases Small-Conductance Ca2+-Activated K+ Current in Patients with Chronic Atrial Fibrillation

Abstract: BackgroundIncreased small-conductance Ca2+-activated K+ current (SK), abnormal intracellular Ca2+ handling, and enhanced expression and activity of Ca2+/calmodulin-dependent protein kinase II (CaMKII) have been found in clinical and/or experimental models of atrial fibrillation (AF), but the cumulative effect of these phenomena and their mechanisms in AF are still unclear. This study aimed to test the hypothesis that CaMKII increases SK current in human chronic AF.Material/MethodsRight atrial appendage tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 34 publications
2
35
2
Order By: Relevance
“…Li et al (2011) showed that SK2 current density is bigger in atrial cells from patients diagnosed with persistent AF (at least 6 months) than in non-AF patients. At a molecular level, CAMKII levels are increased in human AF atrial cells, associated with a left shift of the SK calcium dose-response curve and bigger currents (Fan et al, 2018). Oppositely, in atrial biopsies from chronic AF patients (more than 6 months preceding a medical surgery), the SK1, SK2, (Yu et al, 2012) or SK3 (Skibsbye et al, 2014) transcripts and protein levels are reduced compared with atrial biopsies obtained from patients with sinus rhythm.…”
Section: Atrial Fibrillationmentioning
confidence: 96%
“…Li et al (2011) showed that SK2 current density is bigger in atrial cells from patients diagnosed with persistent AF (at least 6 months) than in non-AF patients. At a molecular level, CAMKII levels are increased in human AF atrial cells, associated with a left shift of the SK calcium dose-response curve and bigger currents (Fan et al, 2018). Oppositely, in atrial biopsies from chronic AF patients (more than 6 months preceding a medical surgery), the SK1, SK2, (Yu et al, 2012) or SK3 (Skibsbye et al, 2014) transcripts and protein levels are reduced compared with atrial biopsies obtained from patients with sinus rhythm.…”
Section: Atrial Fibrillationmentioning
confidence: 96%
“…CaMKII hyperactivity has been demonstrated to be causatively associated with AF and ventricular arrhythmias in heart failure through modulating calcium handling–related protein activities [31, 32]. Recently, research revealed that CaMKII increases small-conductance Ca 2+ -activated K + current in atria from patients with AF [33]. A recent study showed ox-CaMKII–mediated ventricular arrhythmia in a mouse model of Duchenne muscular dystrophy [34].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, contrary to what happens with contraction, the PDE3 or PDE4 control on propensity of 5-HT-evoked arrhythmias on human atrial trabeculae from patients in sinus rhythm or with paroxysmal AF, is lost in persistent AF [93]. 5-HT stimulation has been shown to increase I f [94] and I Ca,L [91,94] in HAMs, but less than β-adrenergic stimulation [91,95] and without regulation of PDE3 or PDE4 [90].…”
Section: Autonomic Remodeling and Upregulation Of Sympathetic Signalingmentioning
confidence: 92%
“…CaMKII has also been shown to autophosphorylate independently of Epac2 in atrial appendage samples of AF patients. Thus, CaMKII autophosphorylation increased Ca 2+ sensitivity of apamin sensitive small-conductance Ca 2+ -activated K + current (I KAS ) in AF [90].…”
Section: Autonomic Remodeling and Upregulation Of Sympathetic Signalingmentioning
confidence: 99%